The intention of young adult to adopt e-wallet during the covid-19 pandemic in Malaysia - Chan, Yao Hui; Chia, Chun Hiang; Loh, Hui Ling; Tong, Essy (2021)
This research is aimed to find out the factors that affect the intention to adopt e-wallet among young adult during the Covid-19 pandemic in Malaysia. This research is using five factors (perceived ease of use, perceived usefulness, perceived privacy and security, government roles, health awareness) to examine their significancy to the intention of Malaysian young adult to adopt e-wallet by referring TAM and UTAUT theory. We selected young adult (18-35 years old) as our research target because they are more familiar with e-wallet. Our research collected 425 responses from Malaysian young adult through Google Forms. SPSS software is applied to examine the reliability and validity of data and find out the relationship between IVs and DV. Pilot test, Cronbach’s Alpha, Pearson Correlation Analysis, and Multiple Regression Analysis are conducted for this purpose. Our result shows that perceived ease of use, perceived usefulness, government roles, and health awareness have a positive relationship with intention of Malaysian young adult to adopt e-wallet. However, we found that perceived privacy and security is insignificant toward the intention of Malaysian young adult to adopt e-wallet. Our research provides several implications to government, ewallet companies, and academia to help them sorting out the current situation of ewallet in Malaysia and how to enhance and promote e-wallets. Lastly, our research provides some limitations and recommendations for future researchers so that they can overcome the limitations and provide more accurate and realistic research.